PERSEPSI DAN KESIAPAN MENIKAH PADA MAHASISWA - Krisnatuti, Diah; Oktaviani, Vivi (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2011)
This research aimed to analyze the correlation between research variables and the influence of college student characteristics, exposure informations, stimulus factors, and knowledge about marriage toward perception and marriage readiness. This research involved 72 college students that were selected by convenient sampling technique. The data was collected through interviews and analyzed using different test, correlation test, and regression test. Research results showed that knowledge about marriage correlated significant with age, sex, and academic achievement. Perception about marriage correlated significant with number of sibling and discussion habit. Perception about marriage was influenced by number of sibling, marriage discussion with friend, and boyfriend. Marriage readiness correlated significant with frequencyto obtain informationabout marriage. Meanwhile, marriage readiness was influenced by students age, number of disease suffered, and the way to manage the household.